Pemerataan Utilisasi Jaringan Multipath dengan Mode Controller Proactive-Reactive pada Software Defined Networking - Akhmad Mukhtarom; Achmad Basuki; Muhammad Aswin (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2017)
Distributing traffic flows on fat-tree network topology used in data center networks is essential. Multipath routing is the common technique used to balance the traffic flows. In Software Defined Networking (SDN), the routing path is fully controlled by a controller to select the optimal path or the multiple paths in order to optimize flows throughput. This paper presents an implementation of a Hydrid proactive and reactive controller mode in SDN to load-balance traffic flows. The controller monitors the path utilization and will reactively install flow-tables to the appropriate switches whenever there are significant traffic spikes for a certain period. For the case of frequently high-utilized paths, the controller will proactively apply flow-tables to the appropriate switches. The evaluation results in a fat-tree topology show that the proposed Hydrid method outperforms LABERIO by 2.38 Mbps higher throughput and 18 seconds lower latency.